(untitled) (Scientific journal of the Fergana State University, 2023)
The article describes the concept of innovation, analyzes foreign literature on this concept. The author also identified a set of personal qualities that determine the innovative potential of the teacher, the characteristics that characterize the innovative activity of the teacher (healthy competition, openness to news, constant self-development) were scientifically substantiated.